MOSCAS SINANTROPICAS PERJUDICIALES, UN DESAFÍO ACTUAL: Musca domestica L. (MUSCIDAE) Y Chrysomya megacephala (FABRICIUS) (CALLIPHORIDAE) - Priscila Maria da Silva Gomes; Angela Mingozzi Martins dos Santos (Universidade do Estado do Rio de Janeiro, 2015)
The synanthropic animals of a particular locality corresponds to some species of wild native fauna that have adapted either temporary or permanently, the new environment modified by human action. Musca domestica and Chrysomya megacephala have a eusinantropico behavior, or their life cycle occurs in anthropized environment. So the article aims to contribute to the characterization of Musca domestica L. (Diptera: Muscidae) and Chrysomya megacephala (Fabricius) (Diptera: Calliphoridae) among the main species of harmful synanthropic flies food health importance. The control populations of harmful synanthropic species requires knowledge of the bionomics of the species. The adoption of advertising campaigns, environmental and health education projects, citizenship, to the biological vector control should be focused on: food waste reduction; Promotion programs (and expansion of existing ones) of basic separation of organic waste, inorganic and risk of domestic origin, commercial and various public and private service activities; Mapping of special areas of risk to public health, especially areas with most polluting activity by human excreta and secretions and domestic animals, organic waste and wastewater focuses exposed to open air, aimed at implementing a continuous system of hygiene and sanitation, integrating the activities of various sectors of society in these areas   DOI: http://dx.doi.org/10.12957/sustinere.2015.20002